Organo-catalytic approach to the enantioselective synthesis of (R)-selegiline - Talluri, Siva Kumar; Sudalai, Arumugam (Tetrahedron, 2007)
An efficient enantioselective synthesis of (R)-selegiline has been achieved by two routes, via proline-catalyzed alpha-aminooxylation as well as alpha-amination of phenylpropanaldehyde as the key step. (c) 2007 Elsevier Ltd. All rights reserved.

Organocatalytic sequential alpha-amination-horner-wadsworth-emmons olefination of aldehydes: enantioselective synthesis of gamma-amino-alpha,beta-unsaturated esters - Kotkar, Shriram P.; Chavan, Vilas B.; Sudalai, Arumugam (Organic Letters, 2007)
A novel and highly enantioselective method for the synthesis of gamma-amino-alpha,beta-unsaturated esters via tandem alpha-amination-Horner-Wadsworth-Emmons (HWE) olefination of aldehydes is described. The one-pot assembly has been demonstrated for the construction of functionalized chiral 2-pyrrolidones, subunits present in several alkaloids.

Organocatalytic sequential alpha-amination/corey-chaykovsky reaction of aldehydes: a high yield synthesis of 4-hydroxypyrazolidine derivatives - Kumar, B. Senthil; Venkataramasubramanian, V.; Sudalai, Arumugam (Organic Letters, 2012)
A tandem reaction of in situ generated a-amino aldehydes with dimethyloxosulfonium methylide under Corey-Chaykovsky reaction conditions proceeds efficiently to give 4-hydroxypyrazolidine derivatives in high yields with excellent enantio- and diastereoselectivities. This organocatalytic sequential method provides for the efficient synthesis of anti-1,2-aminoalcohols, structural subunits present in several bioactive molecules as well.

Optically pure gamma-butyrolactones and epoxy esters via two stereocentered HKR of 3-substituted epoxy esters: a formal synthesis of (-)-paroxetine, Ro 67-8867 and (+)-eldanolide - Devalankar, Dattatray A.; Karabal, Pratibha U.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
The HKR of racemic anti- or syn-3-substituted epoxy esters catalyzed by a Co(III)salen complex provides ready access to the corresponding enantioenriched 3,4-disubstituted gamma-butyrolactones and 3-substituted epoxy esters. This strategy has been successfully employed in the formal synthesis of biologically active 3,4-disubstituted piperidine derivatives, (-)-paroxetine and Ro 67-8867 and a natural product, (+)-eldanolide.

One-pot synthesis of cyclic carbonates from aldehydes, sulfur ylide, and CO2 - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Synlett, 2014)
Treatment of aldehydes with sulfur ylide (CH2=SOMe2 or CH2=SMe2), in the presence of CO2 (1 atm) bubbled sequentially under mild conditions, produces cyclic carbonates in preparative yields. Sodium iodide formed in situ promotes the reaction between epoxide as intermediate and CO2 at ambient conditions, thus constituting a powerful metal-free synthesis of organic cyclic carbonates directly from aldehydes.
Keywords: Carbon dioxide; cyclic carbonates; cyclization; epoxides; Insertion

One-pot highly enantio- and diastereoselective synthesis of anti,anti vinylic 3-amino-1,2 diols via proline catalyzed sequential alpha-amination/benzoyloxyallylation of aldehydes - Ahuja, Brij Bhushan; Sudalai, Arumugam (RSC Advances, 2015)
The first direct asymmetric synthesis of anti, anti vinylic 3-amino-1,2-diols from aldehydes is described via a one-pot sequential L-proline catalyzed alpha-amination/benzoyloxyallylation protocol. The reaction proceeds with exceptionally high diastereoselectivity (>99%) as can be explained based on the Felkin-Ahn transition state model. Its effectiveness is proven unambiguously by demonstrating a short asymmetric synthesis of D-ribo-phytosphingosine tetraacetate (93% ee).

Organocatalytic [4+1]-annulation approach for the synthesis of densely functionalized pyrazolidine carboxylates - Lalwani, Komal G.; Aher, Ravindra D.; Sudalai, Arumugam (RSC Advances, 2015)
A novel one-pot [4+1]-annulation process for the asymmetric synthesis of densely functionalized pyrazolidine carboxylates is described. The in situ generated gamma-hydrazino-alpha,beta-unsaturated ester obtained via proline catalysis acts as a four-atom component, and Corey's sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrazolidine carboxylate units in a highly enantio- and diastereoselective fashion.

Organocatalytic route to enantioselective synthesis of ceramide trafficking inhibitor HPA-12 - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A new organocatalytic approach to the synthesis of ceramide trafficking inhibitor HPA-12 has been described starting from phenacyl bromide. The strategy involves chiral CBS reduction of gamma-ketoester and proline-catalyzed alpha-amination reaction of aldehyde followed by reduction as the key chirality inducing steps. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; CBS reduction; Ceramide; Organocatalytic; Proline